An Inclusive Business Model Innovation in the Delivery of Blended Undergraduate Medical Education - Hibling, Andrew (Graduate School of Business (GSB), 2019)
The World Health Organization predicts that by 2030 there will be a shortage of 1.1 million medical practitioners in Africa. Establishing medical schools is difficult and expensive. Existing schools, albeit under increasing austerity pressure, need to increase their output of medical practitioners. This project aims to explore the implementation of an eLearning ecosystem in medical undergraduate education at the University of Cape Town, as a potentially key component in a blended learning curriculum. This could enable medical schools to use their existing infrastructure, and human and learning resources, to deliver effective off-campus teaching and learning; to increase the number of places available on-campus and, therefore potentially the number of graduating medical practitioners. The project addresses the question of how students would use the eLearning ecosystem, what features they would require, and whether there would be any benefits to students, learning or otherwise. This project employs a qualitative case study design with questionnaires, focus group observations and semi-structured interviews with multiple respondent types including medical and science students, facilitators, and lecturers. An inductive coding process was used to analyse the collected data. Teaching and learning can potentially be offered off-campus by using an eLearning ecosystem with appropriate tools - but only if there significant faculty adoption, students are schooled in digital learning practices and have access to their lecturers and the eLearning ecosystem facilitates off-campus learning opportunities. This project proposes a managed publishing business model innovation to help universities add value by empowering them to deliver a blended learning curriculum.